Distributed Data Storage Strategy in Wireless Sensor Networks - Zhang, Song-juan; Yang, Jian (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to solve the problem of large scalability and low energy efficiency in distributed data storage in wireless sensor networks, the author proposed a temporal-centric storage approach method. By using this method the sensing data are stored in some storage node indexed by a hash function parameterized with detecting time. These nodes act as rendezvous among sink and source nodes. Simulation results show that the proposed approach mitigates the hot-spot problem and can thus improve overall system performance substantially.